2018
DOI: 10.1111/ajt.14984
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining T cell tolerance of alloantigens: Lessons from animal studies

Abstract: Achieving host immune tolerance of allogeneic transplants represents the ultimate challenge in clinical transplantation. It has become clear that different cells and mechanisms participate in acquisition versus maintenance of allograft tolerance. Indeed, manipulations which prevent tolerance induction often fail to abrogate tolerance once it has been established. Hence, elucidation of the immunological mechanisms underlying maintenance of T cell tolerance to alloantigens is essential for the development of nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 194 publications
(377 reference statements)
0
4
0
Order By: Relevance
“…The PD-1/PD-L1 is also predicted to be activated in pre-cDC1s compared to CD8α+ cDC1s, which would be highly beneficial for induction of tolerance in the HCT setting. Interestingly, while PD-1 signaling is critical to induction and maintenance of peripheral tolerance in transplantation, the induction of programmed cell death of alloreactive T-cells has been specifically linked to PD-L1, and its ligand is not believed to be PD-1 [ 53 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…The PD-1/PD-L1 is also predicted to be activated in pre-cDC1s compared to CD8α+ cDC1s, which would be highly beneficial for induction of tolerance in the HCT setting. Interestingly, while PD-1 signaling is critical to induction and maintenance of peripheral tolerance in transplantation, the induction of programmed cell death of alloreactive T-cells has been specifically linked to PD-L1, and its ligand is not believed to be PD-1 [ 53 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…T-cells stimulated with 100μM BEN-exposed FL-BMDCs exhibited a striking increase in PD-1 expression and accelerated proliferation, followed by activation-induced death of half of all allogeneic T-cells in culture. The induction of programmed cell death of alloreactive T-cells has been specifically linked to PD-L1 ( 63 ) and is critical to induction and maintenance of peripheral tolerance in transplantation ( 64 67 ). It is also worth noting that our previous study found that DCs isolated from BEN-treated mice induced less allogeneic T-cell proliferation compared to CY-treated mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have also found that Kupffer cells can induce Tregs to proliferate and secrete IL-10 through direct contact with Tregs while inhibiting T cell activation by secreting PGE2 and 15d-PGJ2 (31)(32)(33)(34). Sinusoidal endothelial cells, as the main components of liver non-parenchymal cells, can induce T cell apoptosis by inducing the expression of PD-L1 and inhibiting T cell secretion of IL-2, thereby inducing immune tolerance (35,36). Meanwhile, studies have shown that hepatic sinusoidal endothelial cells can induce CD4 + T cells to differentiate into CD4 + CD25 low Foxp3specific T cell subsets with inhibitory activity (37).…”
Section: The Immunologic Characteristics Of Livermentioning
confidence: 99%